2016
DOI: 10.1038/srep39182
|View full text |Cite
|
Sign up to set email alerts
|

CREB3L3 controls fatty acid oxidation and ketogenesis in synergy with PPARα

Abstract: CREB3L3 is involved in fatty acid oxidation and ketogenesis in a mutual manner with PPARα. To evaluate relative contribution, a combination of knockout and transgenic mice was investigated. On a ketogenic-diet (KD) that highlights capability of hepatic ketogenesis, Creb3l3−/− mice exhibited reduction of expression of genes for fatty oxidation and ketogenesis comparable to Ppara−/− mice. Most of the genes were further suppressed in double knockout mice indicating independent contribution of hepatic CREB3L3. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 44 publications
(69 reference statements)
3
49
0
Order By: Relevance
“…Conversely, hepatic nuclear CREB3L3 overexpression strikingly attenuated WD-induced hyperlipidemia and atherosclerosis progression in Ldlr -/- mice. As many pieces of literature including ours and the present work confirmed that the primary role of CREB3L3 is regulation of TG metabolism ( Lee et al, 2011, Nakagawa et al, 2016a, Nakagawa et al, 2016b, Nakagawa et al, 2014, Satoh et al, 2020 ), TG per se has been questioned as the major atherosclerosis risk factor, highlighting the cholesterol-related or more comprehensive mechanisms for potential mechanisms of anti-atherogenic effects of CREB3L3.…”
Section: Discussionsupporting
confidence: 69%
“…Conversely, hepatic nuclear CREB3L3 overexpression strikingly attenuated WD-induced hyperlipidemia and atherosclerosis progression in Ldlr -/- mice. As many pieces of literature including ours and the present work confirmed that the primary role of CREB3L3 is regulation of TG metabolism ( Lee et al, 2011, Nakagawa et al, 2016a, Nakagawa et al, 2016b, Nakagawa et al, 2014, Satoh et al, 2020 ), TG per se has been questioned as the major atherosclerosis risk factor, highlighting the cholesterol-related or more comprehensive mechanisms for potential mechanisms of anti-atherogenic effects of CREB3L3.…”
Section: Discussionsupporting
confidence: 69%
“…Of 44 transcription factors previously shown to be differentially expressed between proximal vs distal enterocytes 11 , only one associated with proximal identity, cAMP responsive element binding protein 3 like 3 (Creb3l3), was upregulated in SBR (0.46 average log fold increase in SBR, p<0.0001). Creb3l3 is a master regulator of lipid metabolism 29 , fitting with increased lipid metabolism after SBR. An additional transcription factor, Kruppel-like factor 4 (Klf4) was also increased in SBR (0.26 average log fold increase in SBR, p<0.001).…”
Section: Proximal Si Transcription Factor Creb3l3 Shows Stable Upregumentioning
confidence: 99%
“…In addition, transcription factor PPARα was likely activated in the liver of A. davidianus after prolonged fasting by Upstream Regulator Analysis in IPA. The activated PPARα by fasting promoted the expression of fatty acid oxidation and ketogenesis-related genes in synergy with other fastingrelated transcription factors, such as CREB3L3 (Nakagawa et al, 2016), p300 (Zhang et al, 2016), and PGC-1α (Rodgers and Puigserver, 2007). These results indicate that the enhanced fatty acid oxidation is needed to provide energy for the A. davidianus after prolonged fasting and can also explain why A. davidianus can survive for long periods of food deprivation.…”
Section: Fatty Acid β-Oxidation and Ketogenesis Are Up-regulated Durimentioning
confidence: 79%